Apuntes para la historia de las Islas Canarias 1776-1868 / Francisco María de León ; introducción de Marcos Guimerá Peraza - Guimerá Peraza, Marcos; León y Falcón, Francisco María de (1795-1857) (Biblioteca isleą ; 4)
Índices: p. [373]-402. Bibliografía: p. [403]-407